2016
DOI: 10.1002/bem.21986
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral radiofrequency exposures during adolescence: Impact on astrocytes and brain functions in healthy and pathologic rat models

Abstract: The widespread use of mobile phones by adolescents raises concerns about possible health effects of radiofrequency electromagnetic fields (RF EMF 900 MHz) on the immature brain. Neuro-development is a period of particular sensitivity to repeated environmental challenges such as pro-inflammatory insults. Here, we used rats to assess whether astrocyte reactivity, perception, and emotionality were affected by RF EMF exposures during adolescence. We also investigated if adolescent brains were more sensitive to RF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
0
6
0
2
Order By: Relevance
“…With the widespread use of mobile phones in modern life, adolescents are exposed to radiofrequency (RF) fields from mobile phones and base stations much more frequently than ever. According to one report, 90% of adolescents have a mobile phone and about 40% of them are considered as heavy mobile phone users [ 1 ]. Therefore, this has raised public concerns about the potential health hazard of RF fields on adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…With the widespread use of mobile phones in modern life, adolescents are exposed to radiofrequency (RF) fields from mobile phones and base stations much more frequently than ever. According to one report, 90% of adolescents have a mobile phone and about 40% of them are considered as heavy mobile phone users [ 1 ]. Therefore, this has raised public concerns about the potential health hazard of RF fields on adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of electromagnetic fields on human neurons has been studied for decades [21]. While some studies could not show any neurobiological adverse effects in healthy and vulnerable RF EMF-exposed animals [22], other studies confirm the role of these exposures on neurodevelopment. We have previously reported the findings of our case-control study of children with clinically diagnosed speech problems and the controls.…”
Section: Discussionmentioning
confidence: 99%
“…However, gene responses to GSM-EMF were inconstant from one study to another. In particular, astroglial reactions marked by increased expression of GFAP were observed in response to a unique head-only exposure to GSM-900 MHz (Brillaud et al 2007;Mausset-Bonnefont et al 2004), but was not observed in other studies using either single head-only exposures (Bouji et al 2012;Fritze et al 1997;Watilliaux et al 2011) or repeated head-or whole-body exposures (Court-Kowalski et al 2015;Petitdant et al 2016). The reasons for such discrepancies remain unclear but can result from differences in experimental setting used in the different studies.…”
Section: Introductionmentioning
confidence: 91%